The Politico-Economic Challenges of Ghana's National Health Insurance Scheme Implementation - Adam Fusheini (Kerman University of Medical Sciences, 2016)
Background National/social health insurance schemes have increasingly been seen in many low- and middle-income countries (LMICs) as a vehicle to universal health coverage (UHC) and a viable alternative funding mechanism for the health sector. Several countries, including Ghana, have thus introduced and implemented mandatory national health insurance schemes (NHIS) as part of reform efforts towards increasing access to health services. Ghana passed mandatory national health insurance (NHI) legislation (ACT 650) in 2003 and commenced nationwide implementation in 2004. Several peer review studies and other research reports have since assessed the performance of the scheme with positive rating while challenges also noted. This paper contributes to the literature on economic and political implementation challenges based on empirical evidence from the perspectives of the different category of actors and institutions involved in the process. Methods Qualitative in-depth interviews were held with 33 different category of participants in four selected district mutual health insurance schemes in Southern (two) and Northern (two) Ghana. This was to ascertain their views regarding the main challenges in the implementation process. The participants were selected through purposeful sampling, stakeholder mapping, and snowballing. Data was analysed using thematic grouping procedure. Results Participants identified political issues of over politicisation and political interference as main challenges. The main economic issues participants identified included low premiums or contributions; broad exemptions, poor gatekeeper enforcement system; and culture of curative and hospital-centric care. Conclusion The study establishes that political and economic factors have influenced the implementation process and the degree to which the policy has been implemented as intended. Thus, we conclude that there is a synergy between implementation and politics; and achieving UHC under the NHIS requires political stewardship. Political leadership has the responsibility to build trust and confidence in the system by providing the necessary resources and backing with minimal interference in the operations. For sustainability of the scheme, authorities need to review the exemption policy, rate of contributions, especially, from informal sector employees and recruitment criteria of scheme workers, explore additional sources of funding and re-examine training needs of employees to strengthen their competences among others.